2020
DOI: 10.3390/antiox9090776
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Induced Oxidative Stress Modifies Inflammation and Angiogenesis Biomarkers in Retinal Pigment Epithelial Cells (ARPE-19): Role of CYP2E1 and its Inhibition by Antioxidants

Abstract: The retinal pigment epithelium (RPE) plays a key role in retinal health, being essential for the protection against reactive oxygen species (ROS). Nevertheless, excessive oxidative stress can induce RPE dysfunction, promoting visual loss. Our aim is to clarify the possible implication of CYP2E1 in ethanol (EtOH)-induced oxidative stress in RPE alterations. Despite the increase in the levels of ROS, measured by fluorescence probes, the RPE cells exposed to the lowest EtOH concentrations were able to maintain ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
(115 reference statements)
1
5
0
Order By: Relevance
“…Research performed by Martinez-Gil et al [ 66 ] showed that the antioxidants N-acetylcysteine and diallyl sulfide reduced ethanol-induced increases in CYP2E1 expression and superoxide anions, indicative of a decrease in oxidative stress. These results supported the DAS-induced reduction in oxidative stress in the data presented in this study and a previous study performed by Liu et al [ 67 ] that found DAS attenuated ethanol-induced increases in malonaldehyde (a by-product of lipid peroxidation), lactate dehydrogenase (LDH), and aspartate aminotransferase (AST) in human hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Research performed by Martinez-Gil et al [ 66 ] showed that the antioxidants N-acetylcysteine and diallyl sulfide reduced ethanol-induced increases in CYP2E1 expression and superoxide anions, indicative of a decrease in oxidative stress. These results supported the DAS-induced reduction in oxidative stress in the data presented in this study and a previous study performed by Liu et al [ 67 ] that found DAS attenuated ethanol-induced increases in malonaldehyde (a by-product of lipid peroxidation), lactate dehydrogenase (LDH), and aspartate aminotransferase (AST) in human hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
“…CYP2E1 is an inducible gene that is upregulated under multiple conditions, such as fasting and nutrition intake, as well as in a wide variety of pathophysiological states (2,(12)(13)(14)(15)(16)(17). In addition to metabolizing endogenous substrates and xenobiotics, CYP2E1 is the main source of cellular ROS, and its NADPH oxidase activity is higher than that of other CYP family members (9)(10)(11).…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of CYP2E1 is upregulated in a wide variety of pathological states and diseases, including obesity, diabetes mellitus, alcoholic liver disease, heart diseases, inflammation, Parkinson's disease and cancer (12)(13)(14)(15)(16)(17). In view of the expression characteristic of CYP2E1, it has been used as a therapeutic target in drug discovery and already has been applied in preliminarily studies (18).…”
Section: Introductionmentioning
confidence: 99%
“…Given its functions and anatomical location, RPE is subjected to biomolecule photooxidation, high accumulation of phagosomes, lysosomes, lipid-protein aggregates (such as lipofuscin), and high oxygen tension, which is intensified in retinal dystrophies with loss of photoreceptors ( Sparrrow et al, 2010 ). Accordingly, the mechanisms promoted by RPE cells to counteract the oxidative stress and inflammation involve not only enzymatic defense ( Wunderlich et al, 2010 ), but also the synthesis and release of antioxidant and anti-inflammatory molecules and pro-survival growth factors ( Meyer et al, 2019 ; Martinez-Gil et al, 2020 ). The enzymatic activity of superoxide dismutase (SOD), glutathione peroxidase (GPX), catalase (CAT), peroxiredoxins (PRDXs), and other antioxidant enzymes is essential in RPE to buffer ROS ( Pintea et al, 2011 ; Fang et al, 2016 ).…”
Section: Cellular Responses In the Inherited Retinal Dystrophies In R...mentioning
confidence: 99%